Deciphering the Physical Binding Mechanism of Enzyme–Photosensitizer Facilitates Catalysis-Augmented Photodynamic Therapy - Bingqing Jia; Yang Liu; Xudong Geng; Yuezheng Li; Chengmei Zhang; Yuanyuan Qu; Xiangdong Liu; Mingwen Zhao; Yanmei Yang; Weifeng Li; Yong-Qiang Li (Research)
Enzyme–photosensitizer (PS) conjugates hold great promise for clinical treatment of cancer and infectious diseases via catalysis-augmented photodynamic therapy (PDT). Compared to covalent coupling, physical binding utilizing noncovalent interactions provides a simple and nondestructive strategy to combine PS with enzymes. However, the mechanism of enzyme–PS physical combination remains largely unknown, and physically bonded enzyme–PS conjugates are rarely reported. Here, we systematically investigate the interacting behaviors of representative enzymes with one of the most popular PS of chlorin e6 (Ce6) and elucidate their binding dynamics and crucial determinants. Our results reveal that the positively charged and hydrophobic residues on the surface of enzymes are crucial determinants of Ce6 binding. In addition, we demonstrate that the positively charged surface area of enzymes can be employed as a reliable criterion for assessing and predicting the enzyme–Ce6 binding affinity. Guided by this criterion, we further construct catalase–Ce6 nanoconjugates (CAT–Ce6 NCs) with superior stability and robust photodynamic antimicrobial capability via physical binding. In a showcase treatment of methicillin-resistant Staphylococcus aureus (MRSA)-infected mouse model of subcutaneous abscess, CAT–Ce6 NCs enable hypoxia pathological microenvironment remodeling and bacteria elimination, realizing effective catalysis-augmented PDT. This study deciphers the physical binding mechanism of enzyme–PS and establishes a theoretical framework to facilitate the design and construction of outstanding enzyme–PS NCs for catalysis-augmented PDT.